If it's not what You are looking for type in the equation solver your own equation and let us solve it.
24-6r=6(4-r
We move all terms to the left:
24-6r-(6(4-r)=0
We add all the numbers together, and all the variables
-6r-(6(-1r+4)+24=0
| 4p-5=p=7+5p+2 | | 1+5(2x+3)=96 | | 7y-4=12+36 | | 7=-11+3(b+5)= | | 6.9g+2=4.9g+10 | | G(x)=x2+4x. | | (x-4)^2+((2x+3)-11)^2=45 | | -192=-8(6x+6) | | 20m-29=51 | | 10y=18+4y | | -160=-5(5n+7) | | -160=-5(5n=7) | | X+y=90° | | -t/3=-3 | | 132+24+6x=180 | | -6+y=54 | | 1/3m+5=-8 | | 4n^2+40n+84=0 | | 182=5n+6(8n-5) | | n+174n-8=0 | | v^2-13v+36=) | | 2=-((4-4x)/(-12)) | | 14x=6x+64 | | 4w-9=3w-19 | | 4x-16+7x-175=73 | | 3x²=5x | | 2=-((4-4x)/4) | | 6x+14=3(2x+15) | | 14x-28=9+13x | | 342=x^2+9x+20 | | 14x-28=9 | | 3=u/6+4 |